دور الأمين العام للبلدية في متابعة تنفيذ مداولات المجلس الشعبي البلدي حسب المرسوم التنفيذي 16-320 The Role Of The Municipal Secretary General For The Implementation Of The Communal Peoples Assembly's Deliberations According The Executive Decree Number 16-320 - حميد, عبروس; سعاد, طيبي (Université de M'sila, 2020)
لقد أدت المشاكل المترتبة عن سوء التسيير المحلي و الفشل المتكرر للمجالس الشعبية البلدية في القيام بواجباتها إلى اعادت النظر في مكانة و دور الأمين العام للبلدية، و ذلك من خلال اصدار المرسوم التنفيذي 16-320 المتضمن الأحكام الخاصة المطبقة على الأمين العام للبلدية. حيث تم تعزيز منصبه بتدعيم صلاحياته على مستوى البلدية، خاصة ما تعلق منها بعلاقته مع المجلس الشعبي البلدي، وهذا من خلال جعله المكلف بأمانة جلساته، تحرير مداولاته و تسجيلها، و تنفيذها و نشرها ... الخ، إن هذا الاهتمام من طرف المشرع الجزائري يدل على أن الأمين العام للبلدية يلعب دورا فعالا في تحقيق التنمية المحلية على مستوى البلدية في مختلف المجالات، و هذا من خلال جعله مسيرا و ليس مجرد إداري منفـذ Because of problems arising from maladministration and repeated failures of communal people's assemblies, which led to review of role of the municipal secretary general, by means of executive decree number 16-320 containing special provision applicable to the municipal secretary general. Where they were strengthen his position by empowerment at the municipal level, especially concerning his relationship with communal people's assembly by having the board secretariat, written council s deliberation and implementation and dissemination it. That attention from legislator indicate the municipal secretary general plays an important role to achieve local development in all areas, by make him as a manger not just an implementer
Keywords: البلدية ; المجلس الشعبي البلدي ; الأمين العام للبلدية ; المداولات ; الرقابة الوصائية. ; communal people's assembly ; the municipal secretary general ; deliberations ; municipal decision ; custodial control.